Testicular aging, male fertility and beyond - Dong, Shijue; Chen, Chen; Zhang, Jiali; Gao, Yuan; Zeng, Xuhui; Zhang, Xiaoning (Frontiers in Endocrinology, 2022)
Normal spermatogenesis and sperm function are crucial for male fertility. The effects of healthy testicular aging and testicular premature aging on spermatogenesis, sperm function, and the spermatogenesis microenvironment cannot be ignored. Compared with younger men, the testis of older men due to aging tends to have disturbed spermatogenic processes, sperm abnormalities, sperm dysfunction, and impaired Sertoli and Leydig cells, which ultimately lead to male infertility. Various exogenous and endogenous factors also contribute to pathological testicular premature aging, such as adverse environmental stressors and gene mutations. Mechanistically, Y-chromosomal microdeletions, increase in telomere length and oxidative stress, accumulation of DNA damage with decreased repair ability, alterations in epigenetic modifications, miRNA and lncRNA expression abnormalities, etc., have been associated with impaired male fertility due to aging. In recent years, the key molecules and signaling pathways that regulate testicular aging and premature aging have been identified, thereby providing new strategies for diagnosis and treatment. This review provides a comprehensive view of the underlying mechanisms of aging on spermatogenesis. Furthermore, potential rescue measures for reproductive aging have been discussed. Finally, the inadequacy of testicular aging research and future directions for research have been envisaged to aid in the diagnosis and treatment of testicular aging and premature aging.